Інституційно-правові основи е-дипломатії США - Турчин, Ярина (Видавництво Львівської політехніки, 2016)
The need in the application of new technologies in the professional activity, including diplomatic work appeared under the conditions of the information revolution. One of the means of its implementation is e-diplomacy, which has practical value and is an effective instrument of the state brand formation at the international stage. The term e-diplomacy, indicating the widespread use of information and communication technologies for the fulfillment of its functions by public authorities as weel as communication in the foreign policy sphere, was used for the first time in the United States. The American model of ediplomacy is based on liberal democratic values and a person freedom. It is implemented via a number of famous US Internet industries, such as: Google, Facebook, Twitter and so on. Today the system of the electronic diplomacy belong to the scope of several US agencies, including: the State Department, CIA, Department of Defense, the US Agency for International Development.
Keywords: the USA; e-diplomacy; public diplomacy; services; statutory documents